2022
DOI: 10.1038/s41597-022-01542-9
|View full text |Cite
|
Sign up to set email alerts
|

Dataset of Speech Production in intracranial Electroencephalography

Abstract: Speech production is an intricate process involving a large number of muscles and cognitive processes. The neural processes underlying speech production are not completely understood. As speech is a uniquely human ability, it can not be investigated in animal models. High-fidelity human data can only be obtained in clinical settings and is therefore not easily available to all researchers. Here, we provide a dataset of 10 participants reading out individual words while we measured intracranial EEG from a total… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 84 publications
0
29
1
Order By: Relevance
“…Cometa et al discovered involvement from both cortical and subcortical in syntactic processing, including from the non-dominant hemisphere 15 . Verwoert et al published an open access sEEG dataset of 10 participants reading Dutch words 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Cometa et al discovered involvement from both cortical and subcortical in syntactic processing, including from the non-dominant hemisphere 15 . Verwoert et al published an open access sEEG dataset of 10 participants reading Dutch words 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In the open SEEG dataset [23], ten participants with intractable epilepsy were implanted with SEEG depth electrodes (Dixi Medical, Besancon, France) at the Epilepsy Center Kempenhaeghe in the Netherlands. Intracranial recordings were acquired at 1024 Hz or 2048 Hz using SD LTM amplifiers (Micromed, Treviso, Italy).…”
Section: Open Seeg Datasetmentioning
confidence: 99%
“…Our second aim was to provide appropriate physiological interpretation of our results based on individual contributions of neural features across all available recording sites. Our third aim was to compare our original ECoG dataset against an open SEEG dataset for speech production [23] to elaborate on the overall coverage of brain structures. It must be clearly noted that the effect of feedback on decoding performance was beyond the scope of our analyses.…”
Section: Introductionmentioning
confidence: 99%
“…While such attempts have shown promise, no existing research has reported investigation on logosyllabic languages, such as Chinese and Thai language, for which the speaking population is more than 1.3 billion 15 . In contrast to the alphabetic languages, where words are constructed from combinations of limited size alphabets (e.g., 26 for English), logosyllabic languages employ logographic characters to represent either entire words or single morphemes, which cannot be typed or spelled out directly. Moreover, logosyllabic languages such as Mandarin Chinese have an extensive inventory of over 50,000 logographic characters 16,17 , each with its unique, complex glyph.…”
Section: Mainmentioning
confidence: 99%
“…Most previous studies on language prosthesis use Electrocorticography (ECoG) electrodes 6,11,13,[22][23][24] or Utah array electrodes 4,10,25 to acquire cortical signals. However, some studies show that the subcortical signals have potential to enhance the effectiveness of decoder 26,27 . The current study utilized stereo-EEG to capture both cortical and subcortical neural signals simultaneously from four participants (two males and two females, all young native Mandarin speakers) undergoing intracranial monitoring for epilepsy (Fig.…”
Section: Mainmentioning
confidence: 99%